Mountaineering and Trekking Tourism Management: A Global Perspective (Journal of Tourism and Himalayan Adventures, 2019)
This paper examines the commercialisation of mountains as places for tourism, and attendant impacts on host communities, the natural environments and tourists themselves. Responses to these are many, and these are examined through a framework that identifies various management strategies. Firstly, mountain awareness includes the provision of adequate training and guiding of mountaineering tourists. Secondly, attention needs to be paid to mountain livelihoods of the host communities to ensure that opportunities augment existing options available and impacts are minimised. Lastly, it is important that there is adequate mountain protection through effective management regimes. The paper includes worldwide examples of mountain tourism management, including Nepal, Azerbaijan, Indonesia, Tibet and Tanzania. The ‘seven summits’, or the highest peaks on each of the seven continents are identified with the protected area authority, number of ascents and the current permit costs.